Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar IPAS Kelas III SDN Napunglangir - Dua, Marsela Rinielda; Rawin, Seftiana Clara; Florentino, Mario; Kolo, Yoanita Dewi Roswita; mole, Paulina Nelce (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
To achieve optimal learning outcomes in the Natural and Social Sciences (IPAS) subject, the learning process should be designed and implemented in an active, creative, effective, and engaging manner to maximize students' participation. This study aimed to examine the effect of the Discovery Learning model on the IPAS learning outcomes of third-grade students at SDN Napunglangir. Data were collected through pretests, posttests, and documentation. The tests were administered before and after the students received the instructional treatment. Data were analyzed using validity tests, reliability tests, descriptive statistics, the normality test, and the independent t-test. The findings revealed that the calculated t-value (t = 7.430) exceeded the critical t-value (t = 1.734) at a significance level of 0.05 with 18 df. Therefore, it can be concluded that the Discovery Learning model had a statistically significant effect on the IPAS learning outcomes of third-grade students at SDN Napunglangir.